Breaking the stoichiometric limit in oxygen-carrying capacity of Fe-based oxygen carriers for chemical looping combustion using the Mg-Fe-O solid solution system - Fan, Qianwenhao (2022)
The performance of oxygen carriers contributes significantly to the efficiency of chemical looping combustion (CLC), an emerging carbon capture technology. Despite their low cost, Fe2O3-based oxygen carriers suffer from sintering-induced deactivation and low oxygen-carrying capacity (OCC) during CLC operations. Here, we report the development of a sintering-resistant MgO-doped Fe2O3oxygen carrier with an optimal composition of 5MgO·MgFe2O4, which exhibits superior cyclic stability and an OCC of 0.45 mol O/mol Fe (2.25 mmol O/gsolid), exceeding the widely accepted OCC limit of 0.167 mol O/mol Fe (2.08 mmol O/gsolid) of unmodified commercial Fe2O3. This result distinguishes this report from all past studies, in which efforts to enhance the cyclic stability of Fe-based oxygen carriers would always result in dilution of the OCC. The capacity enhancement by MgO is attributed to the unique mixtures of MgxFe1-xO (halite) and Mg1-yFe2+yO4(spinel) solid solutions, which effectively reduce the exergonicity for the reduction from Fe3+to Fe2+, while preventing any irreversible structural transformations during the redox process. This hypothesis-driven oxygen carrier design approach provides a new avenue for tailoring the lattice oxygen activities of oxygen carriers for chemical looping applications.